Weather architecture - Hill, Jonathan 1958- (Routledge, 2012)
"This book considers climate as well as weather but its principal focus is everyday experience. Weather and climate differ in duration and scale. Unlike the weather, which we can see and feel at a specific time and place, we cannot directly perceive climate because it is an idea aggregated over many years and across a region. Weather Architecture further extends Hill's investigation of authorship by recognising the weather as a creative architectural force alongside the designer and user. Although he acknowledges the influence of the client, contractor and engineer, the relations between the designer, user and weather are the focus of this book. Environmental discussions in architecture tend to focus on the practical or the poetic but here they are considered together. Rather than investigate architecture's relations to the weather in isolation, they are integrated into a wider discussion of cultural and social influences on architecture. The analysis of weather's effects on the design and experience of specific buildings and gardens is interwoven with a historical survey of changing attitudes to the weather in the arts, sciences and society, which leads to a critical re-evaluation of contemporary responses to climate change. At a time when environmental awareness is of growing relevance, the overriding aim is to understand a history of architecture as a history of weather and thus to consider the weather as an architectural author that influences design, construction and use in a creative dialogue with other authors such as the architect and user"--Provided by publisher.